Whitney Bontrager: capstone - Bontrager, Whitney, artist (Colorado State University. Libraries, 2016)
The artist's statement: Ever since I could wrap my hand around a pencil, I have had a love for the visual arts. For me graphic design is so much more than a career choice, it is a complex, visual language that is constantly evolving. Design presents an exciting challenge to me that requires a delicate balance of form and function, fine art and technology, and expression and restraint. As a firm believer in the idea that beauty can be found in the details, I strive to create pieces that embody simple, clean, and elegant layouts. After all, good design is a language that we all speak, and I hope to use my work to make the world a little more interesting to look at.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design